NGHIÊN CỨU NÂNG CAO ĐỘ BỀN VA ĐẬP CỦA POLYME EPOXY BẰNG CÁCH BIẾN TÍNH VỚI LACCOL TÁCH TỪ SƠN TỰ NHIÊN VIỆT NAM - Diệu, Trần Vĩnh; Yến Oanh, Đoàn Thị; Thu, Nguyễn Minh (Vietnam Journal of Chemistry, 2012)
The brittleness or low strain-to-failure is and inherent problem of any high cross-linked thermosets, such as epoxy, unsaturated polyester, and vinylester resins. For epoxy resins, this can be accomplished by a small amount of highly reactive liquid elastomer, for example, carboxylterminated butadiene-acrylonitrile oligomer, which forms a second phase in the cured matrix and impedes its microcracking. In this article, the epoxy-laccol (EP-LC) oligomes were used as modificator to improve impact strength of the epoxy polymer. The laccol (LC) is a natural phenol with two hydroxyl groups in octo-position and long side unsaturated hydrocarbon substitute C17H31. The reaction of the LC with the epoxy resin ED-20 (ED-20:LC = 1:1 eq.) was carried out within 3 hours at 120oC. The reaction product was named EPOLAC. The epoxy-laccol composition with LC content about 20% was prepared by mixing EPOLAC with additional amount of epoxy ED-20. This composition named EL composition. To analyze component content of the composition EL, gas chromatography combines with IR spectroscopy were used. The results show that the LC had not completely reacted with the epoxy resin despite a cooking for 4 hours at 140oC. It still contains some free LC (~3%), as expected, about 15-20% EP-LC monoadduct plus 12-16% EP-LC bisadduct. Some epoxy appears to have homopolymerizied. The composition EL cured with polyethylenepolyamine (120oC, 3 hours) was coated by thin layer 50-60 mm on the surface of different samples. The testing results of mechanical properties show that the polymer layer based on EL composition possesses high impact strength. It is higher 25 times in comparison with the layer without LC. Thus, LC is excellence modificator for epoxy resin. Key words: Impact strength, epoxy resin, laccol.